2022
DOI: 10.1155/2022/3910411
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Familiarity, Foreign Language Speaking Skill, and Foreign Language Anxiety: The Case of Indonesian EFL Learners

Abstract: Since cultural aspects of language learning are not incorporated in some EFL materials and textbooks, this study can be important to investigate the impacts of using cultural-based instruction on developing the speaking skill of Indonesian EFL learners. In addition, this research tried to examine the effects of using cultural-based instruction on foreign language anxiety of Indonesian EFL learners. To reach these aims, the Oxford Quick Placement Test (OQPT) was given to 83 EFL learners, and 50 of them were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…For both instructors and students, this media is captivating, appealing, and simple to create. Additionally, cue cards are immediately recognizable, which can assist students in explaining subjects more easily with lesser preparation time [1,3]. It is possible to reuse image collections, especially when they are covered, so they can suit different levels.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…For both instructors and students, this media is captivating, appealing, and simple to create. Additionally, cue cards are immediately recognizable, which can assist students in explaining subjects more easily with lesser preparation time [1,3]. It is possible to reuse image collections, especially when they are covered, so they can suit different levels.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Cue cards need to be noticeable and long-lasting. As cue card users, learners must therefore take into account the importance, visibility, and timing in the learning process [1,3,50,51]. In addition, some features of the appropriate cue cards have to be considered.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…They asserted that familiarizing with cultural issues can reduce anxiety, and it can be effective in foreign language communication. Using Anderson’s cultural schema theory, Diep et al (2022) found a significant correlation between Indonesian EFL learners’ foreign language anxiety and oral communicative skill. They found out that cultural-based instruction can be a mediating factor in developing oral performance and reducing foreign language anxiety.…”
Section: Review Of Literaturementioning
confidence: 99%